1975
DOI: 10.1136/gut.16.11.887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urogastrone on gastric secretion and plasma gastrin levels in normal subjects.

Abstract: SUMMARY Purified human urogastrone was given by intravenous infusion to 12 normal volunteer subjects and measurements made of gastric acid, pepsin and intrinsic factor secretion, and of plasma gastrin concentration. Clinical, haematological, and biochemical screening tests were made throughout the period of study. Urogastrone inhibited acid and intrinsic factor secretion whether stimulated by pentagastrin, histamine, or insulin, but had a much less marked effect on gastric pepsin output. Plasma gastrin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 9 publications
(7 reference statements)
0
28
0
Order By: Relevance
“…A transformant E. coli strain, YK537(pTA1522), was cultivated in 1.2 liters of TG+1 medium for 6 hr at 37°C. Cells were harvested and treated with 100 ml of osmotic-shock buffer and then with 100 ml of cold water (16). (a) Lyophilized products were dissolved in 6 ml of 25 mM ammonium acetate (pH 5.8), applied to a Sephadex G-50 column (2.5 x 90 cm; particle size, 50-150 ,um), and eluted with the same buffer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transformant E. coli strain, YK537(pTA1522), was cultivated in 1.2 liters of TG+1 medium for 6 hr at 37°C. Cells were harvested and treated with 100 ml of osmotic-shock buffer and then with 100 ml of cold water (16). (a) Lyophilized products were dissolved in 6 ml of 25 mM ammonium acetate (pH 5.8), applied to a Sephadex G-50 column (2.5 x 90 cm; particle size, 50-150 ,um), and eluted with the same buffer.…”
Section: Resultsmentioning
confidence: 99%
“…It is a potent inhibitor of gastric acid secretion (15) and promotes epithelial cell proliferation both in vitro and in vivo (16 (18). Synthetic oligodeoxynucleotides were prepared by a solid-phase method (19).…”
mentioning
confidence: 99%
“…Elder et al, suggested that EGF acts at the parietal cell in the epithelium of the stomach (29), and Forgue-Lafitte et al demonstrated biochemically that there was high 1251 binding in gastric glands isolated from antral and fundic parts of the guinea pig stomach (34). Because gastric glands have heterogeneous cell types, more precise morphologic study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…EGF has been detected in gastric juice (56), and it displays many biologic effects, including inhibition of gastric acid secretion (23,29,57), protection of the gastroduodenal mucosa (53), stimulation of proliferation and differentiation of the epithelium (46), and stimulation of mucin (87) and prostaglandin E production (18). Elder et al, suggested that EGF acts at the parietal cell in the epithelium of the stomach (29), and Forgue-Lafitte et al demonstrated biochemically that there was high 1251 binding in gastric glands isolated from antral and fundic parts of the guinea pig stomach (34).…”
Section: Discussionmentioning
confidence: 99%
“…4 ) Because of its gastric antisecretory activity it may be useful in the treatment of duodenum ulceration. We intended to produce this polypeptide hormone in E. coli using recombinant DNA technology.…”
mentioning
confidence: 99%